Synchronous endometrial and ovarian carcinoma (SEOC); case series and literature review - Lin, Shahzarul Fazril; Yahaya, Zainab; Ramli, Nuraini; Abdul Hamid, Habibah (IMR Press, 2021)
Objectives: Synchronous endometrial and ovarian cancer (SEOC) is a rare female reproductive malignancy comprising ovarian and endometrial cancer. Precise diagnosis is crucial for treatment and prognostication, as overall outcome and treatment is differ from those of metastatic endometrial cancer (EC) or ovarian cancer (OC). In this review based on 4 case series of SEOC, we aim to discuss the clinical characteristic, accurate diagnosis using advance molecular analysis techniques and immunohistochemistry (IHC) tests and treatment modalities of SEOC. Method: Case series and literature review. Results: In our report, SEOCs are more prevalent in young premenopausal women with obesity, nulliparous and hereditary predisposition as risk factors. Abnormal menses, abdominal distention and abdominal pain were the common presenting symptoms. It made all diagnosis for SEOCs histologically based on established criteria. Surgery remains the main treatment modality with the goal for treatment and achieving diagnosis. All of our patients had an endometroid type histology with early stage and low grade histology for both endometrial carcinoma (EC) and ovarian carcinoma (OC) except two patients had concomitant seromucinous ovarian carcinoma (OC). We perform a review of the literature highlighting the characteristic and management of SEOC, particularly emphasizing the importance of IHC test on the histological confirmatory diagnosis and molecular studies. Conclusion: It is very essential to gain an accurate diagnosis, treat and prognosticate this disease as overall outcome and treatment is different compared to metastatic EC or OC.